2015
DOI: 10.3892/ol.2015.3676
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of three networks of genes and microRNAs in adenocarcinoma

Abstract: Abstract. Adenocarcinoma is one of the most serious diseases that threaten human health. Numerous studies have investigated adenocarcinoma and have obtained a considerable amount of data regarding genes and microRNA (miRNA) in adenocarcinoma. However, studies have only focused on one or a small number of genes and miRNAs, and the data is stored in a scattered form, making it challenging to summarize and assess the associations between the genes and miRNAs. In the present study, three networks of genes and miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Using the same approach for the identification of transcription factors, miRNAs, and target and host genes of miRNAs in adenocarcinoma, the regulatory associations between these elements were revealed [ 39 ]. It was found that TP53 directly regulates 9 miRNAs, consisting of hsa-miR-29b-1, hsa-miR-192, hsa-miR-194, hsa-miR-200a, hsa-miR-34a, has-miR-34b, hsa-miR-34c, hsa-miR-145 and hsa-miR-143.…”
Section: Co-expression Of Mirnas With Host Genesmentioning
confidence: 99%
“…Using the same approach for the identification of transcription factors, miRNAs, and target and host genes of miRNAs in adenocarcinoma, the regulatory associations between these elements were revealed [ 39 ]. It was found that TP53 directly regulates 9 miRNAs, consisting of hsa-miR-29b-1, hsa-miR-192, hsa-miR-194, hsa-miR-200a, hsa-miR-34a, has-miR-34b, hsa-miR-34c, hsa-miR-145 and hsa-miR-143.…”
Section: Co-expression Of Mirnas With Host Genesmentioning
confidence: 99%
“…This low cure rate prompted intensive study of possible means of treating osteosarcoma. With progress in molecular biology, treatments for osteosarcoma initially developed from simple surgical excision to individualized limb‐salvage surgery and adjuvant chemotherapy and now include immunotherapy, gene therapy, and targeted therapy. Limb‐salvage surgery is currently applicable for stage IIB osteosarcomas, osteosarcomas in children and pathological fracture associated with osteosarcoma; the its indications for it continue to expand.…”
Section: Introductionmentioning
confidence: 99%
“…The overall survival rates in OS patients have not improved despite recent developments and advances in treatment strategies, prompting rigorous study of possible means of treating OS. Treatments for OS now include gene, targeted, and immunotherapy with progress in molecular biology [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%